Analysis of Spending , Funding and Investment Decisions in Sharia Finance: Funding Decisions , Financing Decisions , Investment Decisions - Intan, Intan safina (Journal of Islamic Economic and Business Studies, 2024)
Monetary decisions important in company For advance riches or pay and upgrade mark organization . Motivation in come back study This is For analyze decision investment , funding and policy dividend nor spending on sharia finance . Study This analyze the decisions made​ to Islamic finance . Research methods This nature qualitative with approach descriptive . Management effective financing of institutions​ Islamic finance is important For guard health finances and reduce risk detrimental financing. Conclusion , research This emphasize importance good working capital and financing management​ in context institution Islamic finance for optimizing liquidity and performance finance , as well manage risk in a way effective .